The Fire Station Book - Bundt, Nancy; Linzer, Jeff. (Minneapolis : Carolrhoda Books, 1981)
Photographs and captions follow a "day in the life" of a fire station, including a fire.
Keywords: Fire stations -- Juvenile literature; Fire departments